An Experimental Study on the Performance Characteristics of a Diesel Engine Fueled with ULSD-Biodiesel Blends - Tran, Viet Dung; Le, Anh Tuan; Hoang, Anh Tuan (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
As a rule, the highest permissible sulfur content in the marine fuel must drop below 0.5% from 1 January 2020 for global fleets. As such, ships operating in emission control areas must use low sulfur or non-sulfur fuel to limit sulfur emissions as a source of acid rain. However, that fact has revealed two challenges for the operating fleet: the very high cost of ultra-low sulfur diesel (ULSD) and the installation of the fuel conversion system and the ULSD cooling system. Therefore, a solution that blends ULSD and biodiesel (BO) into a homogeneous fuel with properties equivalent to that of mineral fuels is considered to be significantly effective. In the current work, an advanced ultrasonic energy blending technology has been applied to assist in the production of homogeneous ULSD-BO blends (ULSD, B10, B20, B30, and B50 with blends of coconut oil methyl ester with ULSD of 10%, 20%, 30% and 50% by volume) which is supplied to a small marine diesel engine on a dynamo test bench to evaluate the power and torque characteristics, also to consider the effect of BO fuel on specific fuel consumption exhaust gas temperature and brake thermal efficiency. The use of the ultrasonic mixing system has yielded impressive results for the homogeneous blend of ULSD and BO, which has contributed to improved combustion quality and thermal efficiency. The results have shown that the power, torque, and the exhaust gas temperature, decrease by approximately 9%, 2%, and 4% respectively with regarding the increase of the blended biodiesel rate while the specific fuel consumption and brake thermal efficiency tends to increase of around 6% and 11% with those blending ratios.